The effectiveness of low velocity (superslow) resistance training - Greer, B. K. (Strength and Conditioning Journal, 2005)
Superslow Training, a form of low-velocity resistance training, is continuing to gain popularity in the U.S. This brief review examines the validity of the Superslow philosophy and its supposed benefits.